Legislative Party Campaign Committees in the American States - Gierzynski, Anthony, 1961- (Book collections on Project MUSE., 1992)
In a time of increasing campaign costs and decreasing state political party activity, legislative party campaign committees have grown to play a major role in the politics of elections in a large number of American states. Anthony Gierzynski's book focuses on these committees. In this first multi-state analysis, Gierzynski explores the nature and practices of the committees through interviews with legislative leaders and staff and through statistical analyses of campaign finance data from ten representative states. In addition to direct cash contributions, legislative caucus campaign committees.